Azimuthal instability of the pulsed positive glow corona and sinuous streamer trace - Bolotov, O.; Golota, V.; Kadolin, B.; Ostroushko, V.; Pashchenko, I.; Zavada, L. (Вопросы атомной науки и техники, 2014)
The numerical simulations of positive corona at the constant voltage less than streamer mode threshold are carried out. The pulse mode based on photon generation and photo-ionization is obtained, and its simple analytical model is proposed. In addition to axially symmetrical process, it is studied the instability of the azimuthal harmonic, in the linear approximation, on the same two-dimensional mesh. It is noted the possible connection of the first harmonic instability with the sinuous streamer trace obtained in photo.